1964
DOI: 10.1113/jphysiol.1964.sp007430
|View full text |Cite
|
Sign up to set email alerts
|

Abomasal secretion and emptying in suckled calves

Abstract: The rumen, reticulum and omasum, the first three compartments of the compound stomach of ruminants, do not develop fully and assume their characteristic digestive functions until the young animal begins to ingest substantial quantities of solid food. When the young calf swallows milk nearly all of it bypasses the reticulo-rumen and flows rapidly through the omasum and into the abomasum as a result of reflex closure of the oesophageal groove.From the point of view of digestive functions the suckled calf is rega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

1969
1969
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 7 publications
4
38
1
Order By: Relevance
“…This is in agreement with other observations made in the calf which showed that the outputs of enzymes were maximal 10-20 min (Grosskopf, 1959 ;Ash, 1964) (Guilloteau et al, 1975 and1979) and the curves of enzyme secretions showed that the trends were similar. Immediately after a meal, the pH was high (about 5) so that the enzymes secreted in large quantities could exert their coagulating activity.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with other observations made in the calf which showed that the outputs of enzymes were maximal 10-20 min (Grosskopf, 1959 ;Ash, 1964) (Guilloteau et al, 1975 and1979) and the curves of enzyme secretions showed that the trends were similar. Immediately after a meal, the pH was high (about 5) so that the enzymes secreted in large quantities could exert their coagulating activity.…”
Section: Methodssupporting
confidence: 82%
“…The patterns of pH and total H + output in relation with feeding agreed with published results (Ash, 1964 ;Hill, Noakes and Lowe, 1970 ;Williams, Roy and Gillies, 1976). The variation of pH in the abomasal pouch was not representative of changes in the pH of the abomasal contents.…”
Section: Methodssupporting
confidence: 80%
“…3 The volume of an ingested fluid meal is the most important determinant of the emptying rate in monogastric animals 4 and suckling calves. 5 Other physiologically important determinants of emptying rate are energy density (ie, caloric content) of a meal, [6][7][8] type of protein or fat, [9][10][11] and osmolarity of the solution. 12 Because an increased caloric content of an ingested meal slows gastric emptying rate, [6][7][8] we hypothesized that an OES containing a high-glucose concentration would be emptied more slowly in suckling calves than a low-glucose OES.…”
mentioning
confidence: 99%
“…The activity of this organ is a subject which has been virtually ignored in recent years, since the currently accepted method of analysing abomasal activity involves the construction of a fistula, a process which precludes investigations during the immediately post-operative period (Ash, 1964). Furthermore, interpretation of the older literature is difficult since it was often not appreciated that enzymes other than rennin could clot milk and that rennin itself could have other protein substrates.…”
Section: Discussionmentioning
confidence: 99%